RESEARCH ON FATIGUE TEST SPECIFICATION FOR TORSION BEAM REAR AXLE - ZHENG SongLin; DENG Xin; FENG JinZhi; WANG HongHai (Jixie qiangdu)
Based on the torsion beam rear axle,the parameters of entire vehicle are analyzed by ADAMS.The result show that the rear axle load is the most significant factor for vertical force amplitude at wheel center.The relationship between vertical force amplitude and displacement amplitude at wheel center are analyzed by Hyper Works.The result show that that the rear axle load is the most significant factor for displacement amplitude at wheel center.By summarizing the existed fatigue test examples for torsion beam rear axle,the relationship is established mathematically between rear axle load and the displacement of torsion beam rear axle.According to the above analysis,the general fatigue test specification for torsion beam rear axles is established.The effectiveness of the new test specification is verified by comparing with old test specification.